An azoospermic male with a novel chromosome 46, XX, der(15)t(Y; 15)(p11.3; p12). Issue 7 (11th July 2022) - Wu, Jiebin; Hu, Guanli; Zhai, Jingfang; Han, Conghui; Li, Zhenbei
Abstract: Male individuals with a 46, XX karyotype are commonly diagnosed with 46, XX male sex reversal syndrome, one of the rarest sex chromosomal anomalies. In this case, we report a rare XX male with Y‐specific DNA sequences located near the end of chromosome 15 p‐arm, which was verified by fluorescent in situ hybridization (FISH) as well as copy number variation sequencing (CNV‐seq) based on the next‐ generation sequencing method (>100 Kb). To the best of our knowledge, there have been no reports of XX male with the Yp region transferred to the terminal of chromosome 15 short arm. Abstract : We report an azoospermia male with a novel chromosome 46, xx, der(15)t(Y; 15)(p11.3; p12) by CNV‐seq combined with traditional karyotype analysis and FISH. To the best of our knowledge, there have been no reports of XX male with the Yp region transferred to the terminal of chromosome 15 short arm.